Partisipasi Civitas Academica STIE Bima melalui Kegiatan Berqurban di Masa Pandemic Covid-19 di Kota Bima - Muniarty, Puji; Wulandari, Wulandari; Hidayanti, Mawar (Dharma: Jurnal Pengabdian Masyarakat, 2021)
The sacrificial activity as a form of community service as one of the tri dharmas of higher education is a means for the active role of the STIE Bima academic community. Eid al-Adha in 2021 will take place during the pandemic, so it will have an impact on the implementation of qurban worship. The form of creative activity driven by the academic community of the STIE Bima educational institution is the arrangement of the schedule for the distribution of sacrificial meat through the order number of distribution coupons. This is in addition to preventing mass crowds in the Covid-19 era in carrying out the PPKM (Enforcement of Community Activity Restrictions) policies implemented by the regional government. It is hoped that the role of the academic community will become a means of literacy in building community participation while still paying attention to health safety in the Covid-19 era. The lecturers carry out the practice of managing sacrificial meat which can be seen from four functions starting from planning, organizing, implementing and supervising. The STIE Bima campus involved the entire academic community, both lecturers and staff, to actively play an active role in the success of the implementation of sacrifices around the campus environment. Community service by the Academic Community of the Bima College of Economics (STIE) in addition to building community enthusiasm, also increases the participation of lecturers and staff to carry out the tri dharma of higher education.